Peran Media Sosial Instagram Sebagai Media Promosi Objek Wisata Tankayo Eco Park - Utami, Fatia; ., Defhany (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This study aims to determine the Role of Instagram Social Media as a Promotional Media for Tankayo Eco Park Sharia Malalo Tourism Object. Role is defined as having a positive meaning and is expected to be able to influence or achieve company goals. The role of Instagram social media is carried out as a result of advances in communication and internet technology which have caused significant changes in consumer behavior in seeking information. To describe this research using the AISAS theory created by Dentsu, 2005, there are 5 elements in this model, namely attention, interest, search, action, and share. This research uses qualitative methods through observation, interviews and documentation. The results showed that the management of the Tankayo Eco Park Syariah tourist attraction made Instagram the main platform in carrying out its promotional activities. Instagram social media acts as a promotional media for Tankayo Eco Park Syariah attractions by posting content in the form of photos and videos to introduce Tankayo to potential visitors carried out by the Instagram admin. Tankayo Eco Park Syariah also receives free promotions obtained through the Instagram accounts of visitors who create content and tag Tankayo Eco Park Syariah Instagram. The use of Instagram social media by Tankayo Eco Park Syariah is able to attract visitors to come directly to the attraction